The band gap and nonlinear optical susceptibility of SrSn1-xVxO3 films - Huang, Ziheng; Ma, Qiushuang; Wang, Depeng; Zhao, Rongjing; Niu, Ruifeng; Wang, Weitian (Frontiers in Materials, 2024)
Perovskite-type oxide SrSn1-xVxO3 thin films with different concentrations x = 0.1–0.9 were fabricated by using pulsed-laser deposition, and the effects of V doping on the structure, optical band gap and the third-order optical nonlinearity were systematically investigated. With the increase of x value, the lattice parameters of SrSn1-xVxO3 decrease from 3.997 to 3.862 Å gradually, while the optical band gaps firstly increase and then decrease with boundary at x = 0.3. The third-order nonlinear optical responses were studied via the z-scan technique. The closed-aperture measurements show a negative nonlinear refractive index n2, and the open-aperture measurements demonstrate a saturable absorption β. Both the n2 and β responses vary with the increase of V doping level. The metal-oxygen chemical bond along with the localized V5+Sn2+V5+ complex contribute to the enhancement of optical nonlinearity, and the highest value of third-order susceptibility χ(3) is observed in SrSn0.5V0.5O3 film.